Mútua exclusão do direito concorrencial à sucessão analisada a qualidade de herdeiro necessário do cônjuge e convivente - Haffers, Laís Mello (2024)
The aim of this paper is to analyze two of the biggest controversies surrounding legitimate succession in Brazil, namely, the possibility of prior exclusion of the right to compete in succesion and the legal status of spouses and cohabitants as necessary heirs. The importance of the work is related to the absence of a specific discussion in the doctrine, which is limited to repeating old and generic concepts, or treating the subject superficially, as well as in view of lege ferenda proposals, which clash with the sense of social justice, given that the matter plays an important role in regulating marital life. Thus, regarding the right to compete in succession, despite the need for its maintenance in the national legal system, the aim is to demonstrate that its early exclusion lege lata is possible, with the support of the balancing technique and the civil-constitutional methodology; the systematic bias; the historical perspective of the proscription; and the literal analysis of the diction of article 426 of the Civil Code. Furthermore, the aim is to demonstrate the need to maintain the spouse as a necessary heir and, on the other hand, the cohabitant as an optional heir. Therefore, we seek to conclude that both of the most controversial issues would be resolved lege lata, with a simple change in ideological stance. Nevertheless, in view of the debates on reforming the Civil Code and the instability and legal uncertainty, at the end, we sought to contribute with a suggested text of the legal provisions commented on throughout the study, as well as the characteristics of the pact clause. The method used is deductive, based on Brazilian and foreign bibliographical research, doctrine, legislation, articles, legal journals, jurisprudence, statistical studies, as well as other sources that are relevant to enriching the work